The cultural geographies of landscape - Minca, Claudio (Hungarian Geographical Bulletin, 2013)
The concept of cultural landscape has been at the core of the scientifi c concerns of generations of geographers and geographical understandings of landscape have also influenced the ways in which modern landscape has been conceived in cognate disciplines. This paper, a modifi ed version of the author’s Inaugural Lecture as Professor of Cultural Geography at Wageningen University, will briefl y refl ect, with the help of some biographical hints, on the nature of Geography and in particular on the ’power of landscape’ for spatial theory and spatial analysis. In the fi nal part of the paper a particular att ention is given to the relationship between the cultural landscape and tourism and travel, envisioned as key expressions of the spatialities of the ‘Modern’.